Don't even think about it ebook - Mlynowski, Sarah (Don't Even Think About It, 2014)
A smart, sassy contemporary teen novel full of romance, secrets, and ESP from the author of  Ten Things We Did (And Probably Shouldn't Have)  and  Bras & Broomsticks ! We weren't always like this. We used to be average New York City high school sophomores. Until our homeroom went for flu shots. We were prepared for some side effects. Maybe a headache. Maybe a sore arm. We definitely didn't expect to get telepathic powers. But suddenly we could hear what everyone was thinking. Our friends. Our parents. Our crushes. Now we all know that Tess is in love with her best friend, Teddy. That Mackenzie cheated on Cooper. That, um, Nurse Carmichael used to be a stripper.  Since we've kept our freakish skill a secret, we can sit next to the class brainiac and ace our tests. We can dump our boyfriends right before they dump us. We know what our friends really think of our jeans, our breath, our new bangs. We always know what's coming. Some of us will thrive. Some of us will crack. None of us will ever be the same.  So stop obsessing about your ex. We're always listening. "Smart and frequently hilarious."— Publishers Weekly , starred “A tour-de-force comic narration that will leave you gasping in awe—if you ever catch your breath from laughing.”—E. Lockhart, author of  We Were Liars “Hilarious, moving, and utterly ingenious.”—Robin Wasserman, author of  The Book of Blood and Shadow  and  The Waking Dark   “Sarah Mlynowski does it again with a fresh, fun, and fabulous story . . . Don’t even THINK about passing up this hilarious read!” —Elizabeth Eulberg, author of  The Lonely Hearts Club   “Funny, realistic, heartfelt, satiric, and unpredictable.” —Ned Vizzini,  New York Times  bestselling author of  It’s Kind of a Funny Story A 2015 Tayshas High School Reading List title 2017 Louisiana Young Readers’ Choice Awards Honor Book 2015-2016 Teen Readers' Choice Stellar Award